The European Consortium on MEN1. Linkage disequilibrium studies in multiple endocrine neoplasia type 1 (MEN1). - Bassett, J; Pannett, A; Forbes, SA; Thakker, R; McCarthy, M; Read, A; Teh, B; Larsson, C; Kytölä, S; Leisti, J; Salmela, P; Weber, G; et al. (1997)
Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder characterised by tumours of the parathyroids, pancreas and anterior pituitary. The MEN1 gene has been localised to a 2-Mb region of chromosome 11q13 by meiotic mapping studies in MEN1 families. Such studies may have a limited resolution of approximately 1 cM (i.e. 1 Mb) and we have therefore investigated 96 MEN1 families (40 British, 17 French, 12 Finnish, 7 Swedish, 7 Dutch, 7 North American, 2 Australian, 1 New Zealand, 1 German, 1 Spanish and 1 Danish) for linkage disequilibrium, in order to facilitate a finer mapping resolution. We have utilised five microsatellite DNA sequence polymorphisms from the candidate region and have accurately determined their allele sizes, which ranged from 161 bp to 272 bp. The heterozygosity and number of alleles (given in brackets), respectively, at the loci were: D11S1883 (76%, 11), D11S457 (55%, 5), PYGM (94%, 18), D11S1783 (10%, 4) and D11S449 (87%, 16). Allelic association was assessed by Chi-square 2 x n contingency tables, by Fisher exact 2 x n contingency tables and by a likelihood-based approach. The results of haplotype analysis revealed 91 different affected haplotypes in the 96 families, an identical affected haplotype being observed in no more than two families. These results indicate the absence of an ancestral affected haplotype. Significant linkage disequilibrium (P < 0.005) could be established amongst the microsatellite loci but not between the loci and MEN1 in either the total population or in any of the geographical sub-populations. The absence of linkage disequilibrium between MEN1 and the polymorphic loci is probably the result of the occurrence of multiple different disease-causing mutations in MEN1.